The HTML pocket guide - Hyslop, Bruce (Peachpit, 2010)
This handy low-priced book is packed with HTML/XHTML definitions and tips, including those for HTML5 elements in depth. Snappy writing and illustrative code samples walk readers through HTML uses and element definitions. Handy pocket size provides a convenient reference for HTML coders. A true companion to standards-compliant design. The HTML Pocket Guide is for both beginning users, who want an introduction to HTML, and more advanced users, who are looking for a convenient reference. While HTML5 is still under development, browser manufacturers are already supporting many of its features in Google Chrome, Firefox, Opera, Safari, and the upcoming Internet Explorer 9. So, now is the time to start learning about it. The HTML Pocket Guide is a valuable companion to creating standards-compliant markup that will help Web designers and developers quickly define content and meaning. Accessible, convenient, and inexpensive, this pocket guide is exactly what web designers and developers need.